2020
DOI: 10.1016/j.neuropsychologia.2020.107331
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of quantifying hemispheric specialisation using fMRI: Evidence from left and right handers on three different cerebral asymmetries

Abstract: Neuroimaging has tremendous potential for quantifying hemispheric specializations.However, the possibilities remain under-utilized, in part, given some of the complexities in quantifying any differences in a reliable, transparent fashion. A second issue with hemispheric asymmetries is that they are extremely one-sided in most people. This skew limits the generalisability of any findings to those participants with rarer forms of cerebral asymmetry. Here, we demonstrate usefulness of an approach developed by Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 90 publications
2
19
0
Order By: Relevance
“…We used fMRI to obtain participant-specific measures of hemispheric dominance for language (word generation task), praxis (tool pantomime task), spatial attention (line bisection judgment task), face recognition (dynamic faces one-back task), and emotional prosody (emotional intonation judgment task). A recent study showed that fMRI can reliably quantify hemisphere asymmetries (47).…”
Section: Methodsmentioning
confidence: 99%
“…We used fMRI to obtain participant-specific measures of hemispheric dominance for language (word generation task), praxis (tool pantomime task), spatial attention (line bisection judgment task), face recognition (dynamic faces one-back task), and emotional prosody (emotional intonation judgment task). A recent study showed that fMRI can reliably quantify hemisphere asymmetries (47).…”
Section: Methodsmentioning
confidence: 99%
“…It is my contention that much of the study of hemispheric specialization and interhemispheric communication (HS/HC) is constrained by conventional wisdom that inhibits the discovery of the developmental processes involved. Indeed, many critical reviews of HS/HC note problems of inadequate statistical power, missing details on proportion of those showing atypical lateralization, and the use of many different, often insufficiently validated, methods to ascertain functional lateralization [3,39,40]. Thus, there are too many instances of failures of replication [41], poor research designs [42], and the accumulation of conflicting evidence that fails to support any explanation of the character of HS/HC (e.g., [43,44]) or for the mechanisms responsible for the specialization [45].…”
Section: Character Of Sciencementioning
confidence: 99%
“…Left-right asymmetry is an important aspect of human brain organization for multiple functions (Coan & Allen, 2004;Corballis, 2003;Hugdahl & Davidson, 2004;Vigneau et al, 2006;Wheeler, Davidson, & Tomarken, 1993;Zago et al, 2017;Zhen et al, 2017). For example, at least 85% of people have left-hemisphere language dominance, based on functional magnetic resonance imaging (fMRI) (Mazoyer et al, 2014), and a similar proportion are right-handed (Gilbert & Wysocki, 1992), although these proportions can vary depending on cut-off values applied to continuous data (Johnstone, Karlsson, & Carey, 2020). Some anatomical features of the brain are also lateralized at the population level, including the overall "torque" or clockwise twisting of the cerebral hemispheres (viewed from below) (Toga & Thompson, 2003), and the anatomy of cortical regions around the Sylvian fissure (Geschwind & Levitsky, 1968), although again the population proportions depend on cut-off values, as well as the precise methods for quantifying asymmetry.…”
Section: Introductionmentioning
confidence: 99%